Kecerdasan Buatan dalam Sistem Pendukung Keputusan Keuangan: Tinjauan Literatur Sistematis (2020–2026) - Amalia Zeta Syarofina; Hamdani Hamdani (Pajak dan Manajemen Keuangan, 2026)
The growing development of Artificial Intelligence (AI) research in the financial industry reflects the increasing integration of advanced technologies into financial activities and services. This growth has prompted scholars to explore which areas of finance are most frequently studied and what types of AI applications are most common in current academic discussions. To address these questions, this study uses a systematic literature review (SLR) by examining journal articles indexed in Scopus, from Q1 to Q4 classifications, published between 2020 and 2026. The initial search identified 907 relevant publications. However, after applying the PRISMA screening and eligibility procedures, only 31 articles met the inclusion criteria and were selected for further review. These studies were analyzed using bibliometric mapping with VOSviewer software and supplemented by qualitative content analysis. The results show that Fintech and risk management are the most widely discussed topics in AI-related financial research. Additionally, Machine Learning is the most prominent AI technology used in the financial sector, especially in fostering innovation, enhancing operational performance, and supporting strategic decision-making. The review also emphasizes that combining Machine Learning and risk management is the most important and rapidly growing area of research within finance.